Nutrition myths - the factor influencing the quality of children's diets - Slávka Mrosková; Ľubomíra Lizáková (University of Ostrava, 2016)
Aim: To analyse the influence of parents' belief in nutrition myths on the frequency of their serving certain foods to their children. Design: Cross-sectional study. Methods: Survey carried out with 297 respondents - parents of children aged 5-18 years. The data collection took place between September 2013 and December 2014. The questionnaire focussed on 14 nutrition myths related to selected foods (milk, dairy products, meat, offal, fruit, vegetables, eggs, fish, legumes, soya, and flour dishes). At the same time, the parents reported the frequency of their serving the monitored foods to their children. In the statistical analysis, Spearman's rank correlation coefficient was used. Results: For nine nutrition myths we found significant negative coefficients between a certain nutrition myth and the frequency of the serving of the food. The nutrition myths related to the consumption of fish (r = -0.328), eggs (r = -0.203), soya (r = -0.301; -0.290), offal (r = -0.155), meat (r = -0.128), milk (r = -0.272; -0.254), and fruit/vegetables (r = -0.104). Conclusion: The belief in nutrition myths appears to be a determinant modifying parental behaviour and subsequently the quality of children's diets.